Small-scale Farmers’ Willingness to Pay for Extension Services: Evidence from Nigeria - SHITU, ADENIPEKUN; Shitu, MAYOWA Victoria; Ojo, Damilola Tina; Nain, Manjeet Singh (Indian Journal of Extension Education, 2025)
Sustainable financing of agricultural extension services remains a major challenge among small-scale farmers in Nigeria. This study examined small-scale farmers’ willingness to pay (WTP) for agricultural extension services in Ikole and Oye Local Government Areas of Ekiti State, Nigeria, using cross-sectional data collected in 2023. Data were obtained through a structured questionnaire and analysed using descriptive statistics and a binary logistic regression model. Willingness to pay for extension services was measured as a binary outcome, with farmers classified as willing or not willing to pay for regular and reliable extension services. The results showed that a substantial proportion of the respondents expressed willingness to pay for extension services. The logistic regression results indicated that education level, farm size, access to extension services, and farming experience significantly influenced farmers’ willingness to pay. Age and gender were not statistically significant determinants. The farmers’ willingness to pay is closely linked to their capacity to benefit from extension services. Strengthening farmers’ awareness of the benefits of extension services and improving service delivery could enhance farmers’ willingness to contribute financially. Policy interventions aimed at improving extension service quality at the local level may promote more sustainable extension financing among small-scale farmers.